2003
DOI: 10.1093/aob/mcg186
|View full text |Cite
|
Sign up to set email alerts
|

Does Ethylene Mediate Cluster Root Formation under Iron Deficiency?

Abstract: Casuarina glauca develops proteoid (cluster) roots in response to Fe deficiency. This study set out to investigate the possible involvement of ethylene in the initiation and/or the morphogenesis of cluster roots (CR). For this purpose, the effect of Ag+ added as silver thiosulfate, an inhibitor of ethylene action has been studied in plants growing hydroponically. No CR formation was observed in these growth conditions. Inhibition of ethylene biosynthesis by aminoethoxyvinylglycine, 1- aminoisobutyric acid, ami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 23 publications
3
25
0
Order By: Relevance
“…Shin and Schachtman (2004), and later Jung et al (2009), demonstrated that ethylene signaling plays a significant role in plant response to stress caused by K deficiency inducing ethylene production, and this in turn affects formation of ROS in the root hair differentiation zone, induces the expression of HAK5 (high-affinity transporter), thus changing root morphology and plant tolerance to nutrient deprivation stress (Shin and Schachtman, 2004). However, this fact was not so certain a few years ago (Zaid et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Shin and Schachtman (2004), and later Jung et al (2009), demonstrated that ethylene signaling plays a significant role in plant response to stress caused by K deficiency inducing ethylene production, and this in turn affects formation of ROS in the root hair differentiation zone, induces the expression of HAK5 (high-affinity transporter), thus changing root morphology and plant tolerance to nutrient deprivation stress (Shin and Schachtman, 2004). However, this fact was not so certain a few years ago (Zaid et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, the involvement of ethylene in P deficiency has been limited to its role in the regulation of morphological responses, like the inhibition of the growth of the main root and the formation of lateral roots, proteoid roots and root hairs [66,[91][92][93][94][95][96]. Nowadays, however, there is evidence that ethylene also plays an important role in the regulation of physiological responses to P deficiency, as is the case with Fe deficiency [5,69,70,97,98].…”
Section: Hormones and Signaling Substances In The Regulation Of Fe Anmentioning
confidence: 99%
“…Results on white lupin indicate that it has no impact on clusterroot formation [29], while in Casuarina glauca inhibition of ethylene biosynthesis results in an inhibition of Fe-deficiency-induced cluster roots [45]. Ethylene may play a role in controlling the length of the cluster-root rootlets, since low ethylene concentrations inhibit lateral root initiation and elongation [46].…”
Section: The Role Of Phytohormones and Sugars In Cluster-root Formationmentioning
confidence: 99%